Failed States in International Relations - Čepilová, Barbora (2010)
The aim of the work Failed States in International Relations is the examination of this phenomenon regarding the terminological discrepancy, causes of the state fragility, security and social aspects and the various attitudes from the side of the international communities. A special part is dealing with so called "successfully failed states" where despite the obvious non-functioning the state is able to survive due to the revenues from the natural resources. The ?ndings are represented on the case study of the Democratic Republic of the Congo - a country with huge potential but miserable performance by now.